Relation of body mass index and work posture to musculoskeletal disorders among fishermen - Yahya Thamrin; Syahrir Pasinringi; A. Muflihah Darwis; Irawan S. Putra (Elsevier, 2021)
Objective: In this study, we researched to determine the relationship between body mass index (BMI) and work posture/position with the musculoskeletal disorders (MSD) in fishermen. Method: This type of research is analytic survey research with a cross-sectional study. There were 224 people as the population in this study with 56 samples as respondents. Nordic Body Map (NBM) and Rapid Entire Body Assessment (REBA) were used as a questionnaire instrument. Results: The result of the Chi-square test shows that the BMI variable has a p-value of p = 0.848 where the p-value is p > 0.05. This means BMI has no significant relationship with MSD. Meanwhile, the work posture/position variable has a p-value of p = 0.000 where the p-value is p < 0.05, which means that there is a significant relationship with MSD. Conclusions: BMI was not associated with MSD. This is possible because fishermen who have normal and abnormal BMI both have complaints of MSD. Meanwhile, work posture/position has a significant relationship with complaints of MSD in fishermen. This is because the posture of fishermen when working with tools when doing research looks very risky.